New types of time domain reflectometry sensing waveguides for bridge scour monitoring. (14th June 2017) - Lin, Chih-Ping; Wang, Kai; Chung, Chih-Chung; Weng, Yu-Wen
Abstract: Scour is a major threat to bridge safety, especially in harsh fluvial environments. Real-time monitoring of bridge scour is still very limited due to the lack of robust and economic scour monitoring device. Time domain reflectometry (TDR) is an emerging waveguide-based technique holding great promise to develop more durable scour monitoring devices. This study presents new types of TDR sensing waveguides in forms of either sensing rod or sensing wire, taking into account of the measurement range, durability, and ease of field installation. The sensing rod is composed of a hollow grooved steel rod paired up with a metal strip on the insulating groove, while the sensing wire consists of two steel strands with one of them coated with an insulating jacket. The measurement sensitivity is inevitably sacrificed when other properties such as the measurement range, field durability, and installation easiness are enhanced. Factors affecting the measurement sensitivity were identified and experimentally evaluated for better arranging the waveguide conductors. A data reduction method for scour-depth estimation without the need for identifying the sediment/water reflection and a two-step calibration procedure for rating propagation velocities were proposed to work with the new types of TDR sensing waveguides. Both the calibration procedure and the data reduction method were experimentally validated. The test results indicated that the new TDR sensing waveguide provides accurate scour depth measurements regardless of the sacrificed sensitivity. The insulating coating of the new TDR sensing waveguide was also demonstrated to be effective in extending the measurement range up to at least 15 m.